Evaluation of the in vitro and in vivo inhibitory effects of Artemisia herba-alba against the growth of piroplasm parasites - Eltaysh, Rasha; Rizk, Mohamed Abdo; El Sayed, Shimaa Abd El Salam; Abouelnasr, Khaled; Abdallah, Abdelnaser Ahmed; Igarashi, Ikuo (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: The effect of Artemisia herba-alba methanolic extract monotherapy and combination therapies on the in vitro growth of several Babesia and Theileria parasites in vitro and mice was investigated in this study. Materials and Methods: Fluorescence assay using SYBR Green I stain was used to evaluate the antibabesial efficacy inhibitory of A. herba-alba either in vitro or in vivo. Hematological parameters in the treated mice were analyzed using a Celltac MEK-6450 computerized hematology analyzer. Results: Artemisia herba-alba reduced the growth of Babesia bovis, Babesia bigemina, Babesia divergens, Theileria equi, and Babesia caballi in vitro in a dose-dependent manner. The in vitro inhibitory impact of A. herba-alba on B. divergens and B. caballi cultures was amplified when combined with either diminazene aceturate (DA). In B. microti-infected mice, a combination therapy consisting of A. herba-alba and a low DA dose inhibited B. microti growth significantly (p < 0.05) better than treatment with 25 mg kg−1 DA. Conclusions: These data show that A. herba-alba, when paired with a modest DA dose, could be a promising medicinal plant for babesiosis treatment. J. Adv. Vet. Anim. Res., 9(2): 267–274, June 2022 http://doi.org/10.5455/javar.2022.i592